Weakened impact of autumn Arctic sea ice concentration change on the subsequent winter Siberian High variation around the late‐1990s. (22nd October 2020) - Chen, Shangfeng; Wu, Renguang; Chen, Wen; Song, Linye; Cheng, Wei; Shi, Wenjing
Abstract: Previous studies suggested that autumn Arctic sea ice concentration (SIC) change around the Kara–Laptev seas has a marked impact on the following winter Siberian High (SH). This analysis reveals that the autumn Arctic SIC‐winter SH connection experienced a marked interdecadal weakening around the late‐1990s according to observational and reanalysis data. Before the late‐1990s, autumn Arctic SIC loss induces pronounced Arctic warming via modulating surface heat fluxes and reduces poleward meridional temperature gradient, which leads to weakening of westerly winds over mid‐latitude Eurasia and contributes to formation of a high‐pressure ridge around Ural mountain. The Ural high‐pressure ridge provides a favourable dynamical condition for the amplification of SH. Consequently, the autumn Arctic SIC‐winter SH connection is strong. In addition, the North Atlantic is dominated by a marked triple sea surface temperature anomaly pattern from autumn to winter, which also partly contributes to a strengthened SH via modulating the Ural high‐pressure ridge. After the late‐1990s, Arctic warming and atmospheric anomalies over Eurasia related to the autumn Arctic SIC loss are much weaker. Accordingly, the autumn Arctic SIC‐winter SH connection is very weak. Changes in the autumn Arctic SIC‐related Arctic warming and atmospheric anomalies are suggested to be related to differences in the autumn Arctic SIC anomalies, with a much weaker amplitude and northward retreat after than before the late‐1990s. Further analysis indicates that the weaker autumn Arctic SIC anomalies over Kara–Laptev seas after the late‐1990s is related to the northward retreat of the mean Arctic SIC. Abstract : Regression maps of winter (a and b) SLP, (c and d) 850‐hPa winds (unit: m·s −1 ), (e and f) SAT anomalies from UDEL onto the normalized inverted SIC index in preceding autumn during 1979–1997 (left) and 1999–2017 (right). Shading regions in (a–b) and (e–f) indicate anomalies significant at the 95% confidence level. Shading regions in (c–d) indicate either component of wind anomalies significant at the 95% confidence level. Contour internals are 0.4 hPa in (a and b), and 0.4°C in (e and f).